Decision Support System for the Selection of Junior High Schools (Smp) in Pasuruan Regency With the Simple Additive Weighting (Saw) Method - Fathonah Nurul Millah; Cindy Taurista (Procedia of Engineering and Life Science, 2021)
Education is important for society. Junior high school (SMP) is an official education located in Indonesia. Learning institutions under the supervision of teachers are called schools. In Pasuruan district there are many schoolsspecially for private junior high schools (junior high schools). Therefore, the selection of the right school is very important because it can affect the next level of education and later work. This research intends to help prospective students choose the right school by utilizing simple additive weighting (SAW) methods into the system. The simple additive weighting (SAW) method isused by the author for the fight with the weighted sum. The results of this study are in the form of a system using python language and flask framework. The end result of this system produces a percentage of 80% which means that this system can help prospective students to determine the right school selection.